Faktor-Faktor Niat Membeli Makanan Berlabel Halal pada Mahasiswa Muslim Yogyakarta - Riyanto Efendi (ITB AAS INDONESIA Surakarta, 2020)
In industrial era 4.0 as now makes the food industry increasingly diverse and easily reaches all walks of life. The food consumed by the community must be good and healthy because every time that is circulated does not necessarily make it healthy and does not have a halal label. By that, the Muslim community must certainly choose foods that are good, healthy, and halal for consumption. So the purpose of this study is to find out the effect of subjective norms, behavioral control perceptions, and religion on the intention to buy halal labeled food for Muslim students. Methodology This study was a quantitative study involving 174 students taken with the 20% Arikunto technique. Methods of multiple linear regression data analysis using SPSS Version 20. The results of the research are as follows: (1). Subjective norms have a positive and significant effect on the intention to buy halal-labeled food for Muslim students, (2). Perceived behavior control has a positive and significant effect on the intention to buy halal-labeled food for Muslim students, (3). Religiosity has a positive and significant effect on the intention to buy halal labeled food for Muslim students, (4). Subjective norms, perceived control behavior, and reliability together influences the intention to buy halal labeled food by 36.8%.